A CONCEPTUAL AND CASE STUDY REVIEW OF THE QUADRUPLE HELIX MODEL OF INNOVATION - Dirkse van Schalkwyk, Riaan; Steenkamp, Rigard (The South African Journal of Industrial Engineering, 2024)
Despite its many pitfalls, the process of innovation should be made as attractive and practical as possible. Innovation model formation is an important yet complex process. This paper reviews the hypothetically improved quadruple helix (QH) model of innovation with respect to model concepts, innovation concepts, and current practical case studies. The updated model constitutes four innovation forces (constructs), namely (1) upscaling agility, (2) triple helix ecosystems, (3) triple management theory (TMT) and triple technology theory (TTT), and (4) epochal society. The model also shows a comprehensive interplay between these constructs within the modern digital, biological, legal and physical worlds. The authors reviewed the model through a conceptual explorative research design with narrative data. The evaluation implied the consideration of combining, adding, or omitting model constructs. Besides learner management and the need to provide a guide for how to use the model, the findings ultimately confirmed its value and usefulness.